CSF HIV RNA Escape in Opsoclonus-Myoclonus-Ataxia Syndrome: Case Report and Review of the Literature - Cabaraux, Pierre; Poncelet, Arthur; Honnorat, Jérome; Demeester, Remy; Cherifi, Soraya; Manto, Mario (Frontiers in Neurology, 2020)
Background: Human immunodeficiency viruses (HIV) infection is associated with a broad range of neurological manifestations, including opsoclonus-myoclonus ataxia syndrome (OMAS) occurring in primary infection, immune reconstitution syndrome or in case of opportunistic co-infection. Case: We report the exceptional case of a 43-year-old female under HIV treatment for 10 years who presented initially with suspected epileptic seizure. Although the clinical picture slightly improved under anti-epileptic treatment, it was rapidly attributed to OMAS. The patient exhibited marked opsoclonus, mild dysarthria, upper limbs intermittent myoclonus, ataxia in 4 limbs, truncal ataxia, and a severe gait ataxia (SARA score: 34). The diagnostic work-up showed radiological and biological signs of central nervous system (CNS) inflammation and cerebral venous sinus thromboses. The HIV viral load was higher in cerebrospinal fluid (CSF) than in the blood (4,560 copies/ml vs. 76 copies/ml). She was treated for 5 days with pulsed corticotherapy. Dolutegravir and anticoagulation administration were initiated. Follow-ups at 2 and 4 months showed a dramatic improvement of clinical neurologic status (SARA score at 4 months: 1), reduction of CNS inflammation and revealed undetectable CSF and serum viral loads. Conclusion: This case underlines the importance of the evaluation of the CSF viral load in HIV patients developing OMAS and suggests CSF HIV RNA escape as a novel cause for OMAS.